Advances in Multiscale and Multifield Solid Material Interfaces - Rizzoni, Raffaella; Lebon, Frédéric; Dumont, Serge; Serpilli, Michele (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Interfaces play an essential role in determining the mechanical properties and the structural integrity of a wide variety of technological materials. As new manufacturing methods become available, interface engineering and architecture at multiscale length levels in multi-physics materials open up to applications with high innovation potential. This Special Issue is dedicated to recent advances in fundamental and applications of solid material interfaces.